The effect of corporate governance mechanisms and their interactions on earnings quality / Nasrin Azar - Nasrin , Azar (2020)
Corporate governance (CG) mechanisms play an essential role in improving financial reporting quality, especially earnings quality. Due to corporate failures around the world, there has been a renewed interest in the effect of CG on earnings quality. The primary objectives of this thesis are to (1) investigate the impact of CG characteristics on earnings quality, and (2) examine whether the interactions between CG mechanisms influence earnings quality. Based on the agency and resource dependence theories, this study develops and examines ten main hypotheses (23 sub-hypotheses) to achieve these objectives. This study identifies CG mechanisms such as the board of directors, audit committee, external audit, and internal audit as well as the interaction among them. Earnings quality is measured using primary qualitative characteristics of accounting information (relevance and faithful representation of earnings) defined by FASB's/IASB's Conceptual Framework (2010). Relevance is operationalised by predictive value (PV) and confirmatory value (feedback value) (FV) of earnings. Faithful representation is defined by neutrality's concept using abnormal accrual. The analysis utilises panel data of 484 non-financial firms listed on the Malaysian Stock Exchanges for years 2007-2013. This study tests hypotheses using univariate and multivariate techniques. The appropriate regression model is Generalised Least Square (GLS). Further analyses, such as specification tests and sensitivity tests (OLS regression), are conducted. The results show that all board characteristics have a significant effect on PV and FV of earnings. However, board size has a negative association with them. All board characteristics have a significant relationship with neutrality except for board meetings frequency. However, the direction is positive for board independence and non-CEO duality. Board quality has a significant positive association with earnings quality. Audit committee independence and meetings frequency show a significant and positive influence on PV. Except for the audit committee meeting, none of the audit committee characteristics affects FV. Audit iv committee meetings frequency and independence are significantly and positively, while audit committee size is significantly and negatively related to the neutrality of earnings. Audit committee expertise is not associated with the neutrality of earnings. Audit committee quality is positively associated with earnings quality. Internal audit experience has a significant positive impact on PV and neutrality of earnings, while there is no significant relationship between that and FV. Internal audit independence is negatively and significantly related to PV, FV, and neutrality of earnings. Internal audit quality also has no significant influence on PV and FV but has a significant negative effect on the neutrality of earnings. All external audit characteristics are positively and significantly related to PV. However, regarding FV and neutrality, there is no significant relationship between external audit size and them. External audit quality is significantly and positively related to earnings quality. Interactions between CG mechanisms have joint effects on earnings quality except for the interaction between board and internal audit quality, which follows substitution effects. This study contributes to the existing literature by using interaction among CG mechanisms and describing earnings quality based on FASB's/IASB's Conceptual Framework. The findings could be useful to users of accounting information, standard-setters, and regulators in reconsidering how the quality of monitoring mechanisms is improved and thus promote the fundamental qualitative characteristics of earnings.